Assessment of language proficiency in bilinguals: Relevance for bilingual education - Prema K S; Mekhala V G (Journal of All India Institute of Speech and Hearing, 2013)
Consequent to globalization, proficiency in language has become an integral part in the domain of education. With the prevailing bilingualism in the educational set-up, there is a need to explore if we are geared to meet the challenges of bilingual education. Two studies were conducted in this direction. The first study focused on development of language proficiency assessment tool for Kannada-English bilinguals with primed Lexical Decision Task (LDT) paradigm (online task) validated with self rating questionnaire, LEAP-Q (offline task). The reaction time obtained on LDT was compared with the scores on LEAP-Q. The results indicated positive correlation between translation equivalent pairs of LDT and LEAP-Q suggesting that primed LDT could serve as a test for bilingual proficiency. In the second study, fifteen teachers who are non-native speakers of Kannada and English were tested for language proficiency using the online task. The results indicated that the teachers, although residing in Kannada speaking areas for long years, were less proficient in Kannada (mother tongue of children) compared to English (the medium of instruction). The outcome of the study has implications for educational policy makers and teacher educators in countries where bilingualism and multilingualism in education has been a challenge